Uncommon Diseases: a Look from Pediatrics - Jan Oneil González Ramos; Lisbel Aguilar Lezcano (Revista Finlay)
Uncommon diseases are a high rate cause of death and of a low prevalence as well. In general they present a chronic quite severe progress, with multiple motor, sensory and cognitive disabilities and therefore they use to show a high level of clinical complexity which makes their identification and diagnosis very difficult. Most of them are of genetic origen, but the environmental component should always be considered even in those understood as monogenic. Uncommon diseases have been and will continue to be a challenge since these pathologies in Cuba are treated when there appear associated to other and not as a particular condition.